Carajás: crescimento do produto social, da pobreza e da degradação ambiental na Amazônia - Maurílio de Abreu Monteiro (Confins)
The article analyzes what underpinned, in the first two decades of the 21st century, the economic growth of the Amazon region of Carajás, far above what occurred in other Brazilian regions. It demonstrates that such growth resulted from the previous existence of an export structure, equipped with a sector with very high labor productivity and infrastructure that enabled it to overcome spatial barriers, a configuration that allowed a rapid response to the growing global demand for commodities. It reveals that, despite the extremely high regional economic growth, there was a deepening of the primary exporting character of the economy and a strengthening of environmentally harmful dynamics. A context in which, regionally, extreme poverty declined more slowly than at the national level, with, however, an increase in the intensity and severity of poverty and the number of poor people in the region.